Preliminary Phytochemical and Cytotoxic Activity of The Aqueous and Chloroform Fractions of The Leaf of Persea Americana Mill (Lauraceae) - Ikpefan, E. O.; Ayinde , B. A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The preliminary phytochemical and cytotoxic effects of the chloroform and aqueous fractions of the methanol extract of the leaves of Persea americana were carried out. Cytotoxicity was carried out using tadpoles of Ranniceps raninus at 20-400 ?g/ml. The methanol extract was subjected to solvent partitioning and chromatographic procedures guided by cytotoxic tests. Phytochemical screening results revealed the presence of saponins, flavonoids, tannins and cardiac glycosides .The chloroform fraction of the leaf extract produced 100 % tadpole mortality at 200 ?g/ml. Chromatographic analysis of the active chloroform fraction yielded a compound (CH-B2) which gave a tadpole mortality of 96.70 ±3.33 % at 10 ?g/ml. Cytotoxicity results showed that the chloroform fraction had an LC50 of 10.77 ?g/ml while the its VLC sub-fractions 4 and 5 and isolated compound had LC50 of 4.67, 18.0 and 3.33 ?g/ml respectively. The results support the folkloric use of the plant in treating tumor related ailments. However, further work need to be carried out to establish the identity of the isolated compound.